Establishing the cross‐cultural applicability of a harmonized approach to cognitive diagnostics in epilepsy: Initial results of the International Classification of Cognitive Disorders in Epilepsy in a Spanish‐speaking sample. Issue 3 (24th January 2023) - Reyes, Anny; Salinas, Lilian; Hermann, Bruce P.; Baxendale, Sallie; Busch, Robyn M.; Barr, William B.; McDonald, Carrie R.
Abstract: Objective: This study was undertaken to evaluate the cross‐cultural application of the International Classification of Cognitive Disorders in Epilepsy (IC‐CoDE) to a cohort of Spanish‐speaking patients with temporal lobe epilepsy (TLE) living in the United States. Methods: Eighty‐four Spanish‐speaking patients with TLE completed neuropsychological measures of memory, language, executive function, visuospatial functioning, and attention/processing speed as part of the Neuropsychological Screening Battery for Hispanics. The contribution of demographic and clinical variables to cognitive performance was evaluated. A sensitivity analysis was conducted by examining the base rates of impairment across several impairment thresholds. The IC‐CoDE taxonomy was then applied, and the base rate of cognitive phenotypes for each cutoff was calculated. The distribution of phenotypes was compared to the published IC‐CoDE taxonomy data, which utilized a large, multicenter cohort of English‐speaking patients with TLE. Results: Across the different impairment cutoffs, memory was the most impaired cognitive domain, with impairments in list learning ranging from 50% to 78%. Application of the IC‐CoDE taxonomy utilizing a −1.5‐SD cutoff revealed an intact cognitive profile in 47.6% of patients, single‐domain impairment in 23.8% of patients, bidomain impairment in 14.3% of patients, and generalized impairment in 14.3% of the sample. This distribution was comparable to the phenotype distribution observed in the IC‐CoDE validation sample. Significance: We demonstrate a similar pattern and distribution of cognitive phenotypes in a Spanish‐speaking epilepsy cohort compared to an English‐speaking sample. This suggests stability in the underlying phenotypes associated with TLE and applicability of the IC‐CoDE for guiding cognitive diagnostics in epilepsy research that can be applied to culturally and linguistically diverse samples.